2013
DOI: 10.1016/j.jsat.2013.02.005
|View full text |Cite
|
Sign up to set email alerts
|

Initiation of buprenorphine during incarceration and retention in treatment upon release

Abstract: We report here on a feasibility study of initiating buprenorphine/naloxone prior to release from incarceration and linking participants to community treatment providers upon release. Study consisted of a small number of Rhode Island (RI) prisoners (N=44) diagnosed with opioid dependence. The study design is a single arm, open-label pilot study with a 6-month follow up interview conducted in the community. However, a natural experiment arose during the study comparing pre-release initiation of buprenorphone/nal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
55
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(57 citation statements)
references
References 35 publications
1
55
0
1
Order By: Relevance
“…These results are comparable to those reported by Zaller et al (2013) in their small-scale feasibility study. It is noteworthy that rates of post-release treatment entry were similar for the In-Prison Buprenorphine Conditions and the Condition in which participants did not start buprenorphine in prison and were referred to the OTP in the community, (44%, 51%, and 44%, respectively) as the Condition involving counseling only in prison and referral to the CHC had by far the lowest rate of community treatment entry (22%).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…These results are comparable to those reported by Zaller et al (2013) in their small-scale feasibility study. It is noteworthy that rates of post-release treatment entry were similar for the In-Prison Buprenorphine Conditions and the Condition in which participants did not start buprenorphine in prison and were referred to the OTP in the community, (44%, 51%, and 44%, respectively) as the Condition involving counseling only in prison and referral to the CHC had by far the lowest rate of community treatment entry (22%).…”
Section: Discussionsupporting
confidence: 90%
“…All 9 were on relatively low doses (1–3 mg) when they discontinued. In the study by Zaller et al (2013), 12 non-tolerant participants with pre-incarceration opioid dependence were on buprenorphine for, on average, one week until release from incarceration; of these, 11 continued buprenorphine treatment in the community; one participant (8.3 %) did not like the effects of the medication and entered drug-free treatment. Garcia et al (2007) reported that of the 45 participants (most of whom were opioid-tolerant) who began buprenorphine treatment in prison, two (4.4%) withdrew because of side effects attributed to the medication.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is particularly the case for individuals with substance use disorders who may have insufficient access to addiction treatment within correctional settings and poor linkage to substance use treatment upon release (McKenzie, Macalino, McClung, Shield, & Rich, 2005). The incarcerated setting represents a significant public health opportunity to engage drug-involved offenders in substance use treatment as well as other evidence based re-entry services (Boutwell, Nijhawan, Zaller, & Rich, 2007; Perry et al, 2013; Zaller et al, 2013). …”
Section: Discussionmentioning
confidence: 99%